2014
DOI: 10.1088/0953-8984/26/13/135901
|View full text |Cite
|
Sign up to set email alerts
|

Marble game with optimal ferroelectric switching

Abstract: A low coercivity and, consequently, low hysteresis loss are desired properties for ferroelectric materials used in high-power and high-frequency actuators. The coercive field required for the onset of ferroelectric switching is shown to develop a strong directional anisotropy due to peculiarities of an energy surface associated with the polarization rotation. It is found that the ferroelectric anisotropy exhibits 'hard' and 'easy' switching axes similar to magnetic materials. The hard axis corresponds to 180° … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…. Though these coercive fields are comparable to values suitable for integration to silicon chips (E c ≈ 50 kV cm −1 ), applications such as high-power actuators and low-voltage logic and memory elements ask for ferroelectrics with robust polarizations that can be switched by a lower coercive field [12][13][14][15] . Ultra-low coercive fields as low as 5 kV cm −1 were observed in pulsed laser deposition grown Ca 3 Ti 2 O 7 thin films, but the reason behind this reduction (and whether it is an intrinsic or an extrinsic effect) is not clarified yet 16 .…”
mentioning
confidence: 99%
“…. Though these coercive fields are comparable to values suitable for integration to silicon chips (E c ≈ 50 kV cm −1 ), applications such as high-power actuators and low-voltage logic and memory elements ask for ferroelectrics with robust polarizations that can be switched by a lower coercive field [12][13][14][15] . Ultra-low coercive fields as low as 5 kV cm −1 were observed in pulsed laser deposition grown Ca 3 Ti 2 O 7 thin films, but the reason behind this reduction (and whether it is an intrinsic or an extrinsic effect) is not clarified yet 16 .…”
mentioning
confidence: 99%
“…These measurements are in agreement with our previous numerical studies that predicted this phenomenon. Furthermore, the predictions in [ 3 ] indicated that the coercive field is highly anisotropic, and it was anticipated that the ferroelectric hysteresis would be sensitive to the direction of the applied electric field. The first principles modelling used in [ 1 3 ] differs from most macroscopic phenomenological modelling since the total energy losses in the former model are linked to the coercive field that opposes the external electric field.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the predictions in [ 3 ] indicated that the coercive field is highly anisotropic, and it was anticipated that the ferroelectric hysteresis would be sensitive to the direction of the applied electric field. The first principles modelling used in [ 1 3 ] differs from most macroscopic phenomenological modelling since the total energy losses in the former model are linked to the coercive field that opposes the external electric field. For the macriscopic phenomenological approach, the mechanical losses and the electric losses are often approximated separately and have been of great value in characterizing the losses of resonant or non-resonant driving of piezoelectric actuators [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations